Static Stability of Derrick with Double Flat Arm. Issue 1 (June 2020) - Liao, Yun; Lin, Guanglong; Wang, Dehong; Li, Wenbin; Ye, Huawei; Hua, Cheng; Ma, Chi; Zhu, Jinlin; Dong, Qi; Ju, Yanzhong
Abstract: In order to investigate the stability of a derrick under wind load, a floor type double flat arm derrick is selected as the object, and the numerical simulation method is applied for the eigenvalue buckling analysis and the nonlinear stability analysis to get the instability mode and the critical wind speed in static stability. The results show that the position where the derrick first buckles is the connection between the derrick and the flat arm, and finally the torsional instability leads to the overall instability. The instability of the derrick without waist ring is caused by the damage of the main material of the tower leg. The mean wind speed in static instability is 56 m/s.